(untitled) (European Journal of Formal Sciences and Engineering, 2025)
The number of firms involved in the production of barrels from white oak (quercus petraea L,) is small. The production of wood barrels is quite complex and with a low exploitation coefficient. We think it is in the interests of firms to know how much the coefficient of use of sawn material for these types of products is. For the study we have chosen the firm "BehaN" in Rahovec, which mainly deals with the production of oak wood barrels. The sawn material taken in the study was of a good quality. To do the tests we used weighing methods, as its volume was difficult to measure since it was half milled. Tests were conducted for the production of barrel details with a volume of 50, 30 and 20 litters, which are most widely used by the costumers. For the realization used by the firm were taken into account the dimensions and technology. From the measurement data it turned out that the weight of the sawn timber was about 250kg. The results of these weights were exchanged in volume and percentage and they are shown in final results.